Coagulation of Synthetic Contaminated Water with Lead (II) Metal by ‎Using Kaolin and Bentonite with Alum (Journal of University of Babylon for Engineering Sciences, 2024)
The present study examines the susceptibility of both bentonite clay and kaolin as  coagulant aids with alum to the removal of lead metal from synthetic contaminated water two levels of lead(II) contamination were taken (10,20 )mg/l by using lead nitrate  .Use the Jar test to represent coagulation and flocculation after determining the optimum dose and medium for all coagulants different proportions of both clays were taken with alum the results were the best removal to lead (II) with 20 mg/l (75% bentonite : 25% alum ) 94.1%, (40% kaolin : 60% alum ) 91.2% and the best removal to lead (II) with 10 mg/l( 40% bentonite : 60% alum) 92.02 %  , (75% kaolin : 25% alum ) 90% . After the treatment , the sludge for  the best removal was taken and divided into three sections once used directly and again for regeneration using a base solution once and an acid solution for different periods. The best lead(II) removal was achieved when using the sludge directly, which does not deny that the regeneration of the sludge was also a good removal. The best removals were (85, 85.9, 84, 86)